2017
DOI: 10.5056/jnm16201
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Deoxycholic Acid on Secretion and Motility in the Rat and Guinea Pig Large Intestine

Abstract: Background/AimsBile acid is an important luminal factor that affects gastrointestinal motility and secretion. We investigated the effect of bile acid on secretion in the proximal and distal rat colon and coordination of bowel movements in the guinea pig colon. MethodsThe short-circuit current from the mucosal strip of the proximal and distal rat colon was compared under control conditions after induction of secretion with deoxycholic acid (DCA) as well as after inhibition of secretion with indomethacin, 1,2-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Bile acid malabsorption (BAM) has been widely implicated in the development of diarrhea, including diarrhea caused by the tyrosine kinase inhibitor neratinib [49] and in patients with GI-GvHD [50], increasing colonic secretion of water and electrolytes and the induction of propagated contractions [51]. We identified changes in plasma bile acids and ileal gene expression following melphalan, indicative of BAM.…”
Section: Discussionmentioning
confidence: 97%
“…Bile acid malabsorption (BAM) has been widely implicated in the development of diarrhea, including diarrhea caused by the tyrosine kinase inhibitor neratinib [49] and in patients with GI-GvHD [50], increasing colonic secretion of water and electrolytes and the induction of propagated contractions [51]. We identified changes in plasma bile acids and ileal gene expression following melphalan, indicative of BAM.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical studies have shown that the increase in total fecal BAs is significantly correlated with abdominal pain and accelerated colonic transit in patients (15, 16). Animal studies also showed that BAs directly induce accelerated colonic motility and visceral hypersensitivity (17, 18). Conversely, attenuation of BA excretion with sequestering agents partially alleviated the symptoms of IBS-D patients (19, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings provide an explanation for the fact that the most effective therapeutic agents for diarrhea and constipation are known to alter both chloride secretion and motility. These includes 5-hydroxytryptamine receptor 4 agonists and other prokinetic agents [ 64 , 65 ], prosecretory drugs, such as lubiprostone [ 66 , 67 , 68 , 69 ], and high concentrations of bile acids, such as deoxycholic acid [ 70 ]. The relationship between gut motility and fluid secretion provides insights into how prokinetic drugs can contribute to increasing stool moisture content and volume, address the constipation caused by CF, and have the potential to cause diarrhea and fluid loss.…”
Section: Discussionmentioning
confidence: 99%